Point-of-Care Mobile Application to Guide Health Care Professionals in Conducting Substance Use Screening and Intervention: A Mixed-Methods User Experience Study - O'Grady, Megan A.; Kapoor, Sandeep; Gilmer, Evan; Neighbors, Charles J.; Conigliaro, Joseph; Kwon, Nancy; Morgenstern, Jon (ACI Open, 2019)
Background Well-documented barriers have limited the widespread, sustained adoption of screening and intervention for substance use problems in health care settings. mHealth applications may address provider-related barriers; however, there is limited research on development and user experience of such applications.Objective This user experience study examines a provider-focused point-of-care app for substance use screening and intervention in health care settings.Method This mixed-methods study included think-aloud tasks, task success ratings, semistructured interviews, and usability questionnaires (e.g., System Usability Scale [SUS]) to examine user experience among 12 health coaches who provide substance use services in emergency department and primary care settings.Results The average rate of successful task completion was 94% and the mean SUS score was 76 out of 100. Qualitative data suggested the app enhanced participants' capability to complete tasks efficiently and effectively. Participants reported being satisfied with the app's features, content, screen layout, and navigation and felt it was easy to learn and could benefit patient interactions. Despite overwhelmingly positive user experience reports, there were some concerns that the app could negatively affect patient interactions due to reductions in eye contact and ability to build rapport.Conclusion Using the “Fit between Individuals, Task, and Technology” framework to guide interpretation, overall results indicate acceptable user experience and usability for this provider-focused point-of-care mobile app for substance use screening and intervention as well as favorable potential for adoption by health care practitioners. Such mobile health technologies may help to address well-known challenges related to implementing substance use services in health care settings.
Keywords: SBIRT; mHealth; screening; substance use; usability; user experience